Muscular wall replacement of the ileocecal valve after necrotizing enterocolitis resembles ileocecal atresia: Report of two cases and management - Daniel A. Galvis (Elsevier, 2021)
Atresia of the ileocecal valve is an extremely rarely described phenomenon, with only 11 cases previously reported in the literature. We present two cases resembling atresia, both of which were in premature infants who presented with obstruction after recovering from necrotizing enterocolitis. The apparent atresia was more likely a discrete stricture of the ileocecal valve. Both were successfully treated with ileocecectomy and primary anastomosis.